Income inequality and the international transfer of environmental values - Jasper N. Meya; Moritz A. Drupp; Nick Hanley (Kiel University, Department of Economics, 2018)
How the valuation of environmental goods is related to income is a key question for economics, but the role of income inequality is often neglected. We study how income inequality affects the international transfer of the estimated value of environmental goods from a study to a policy site - a practice called value or benefit transfer. Specifically, we apply theory-driven, structural transfer factors to examine whether adjusting for income inequality affects errors made in benefit transfer, drawing on a multi-country valuation study on water quality improvement. Our convergent validity analysis shows that the structural income inequality adjustment reduces benefit transfer errors by more than 1.5 percentage points on average across all transfers. The adjustment for inequality is particularly important when income is distributed more unequally at the policy site relative to the study site, yielding reductions in transfer errors of up to 33 percentage points. Our results highlight the importance of taking the effects of economic inequality into account and are relevant for environmental valuation as well as public policy appraisal.
Keywords: Q51; H43; D31; D61; D63; Q53; Q25; 330; environmental valuation; income inequality; benefit transfer; policy appraisal; transfer errors